Fetal Tachycardia in the Setting of Maternal Intrapartum Fever and Perinatal Morbidity - Tita, Alan T. N.; McGee, Paula L.; Reddy, Uma M.; Bloom, Steven L.; Varner, Michael W.; Ramin, Susan M.; Caritis, Steve N.; Peaceman, Alan M.; Sorokin, Yoram; Sciscione, Anthony; Carpenter, Marshall W.; Mercer, Brian M.; Thorp, John M.; Malone, Fergal D.; Buhimschi, Catalin; for the Eunice Kennedy Shriver National Institute of Child Health Human Development Maternal-Fetal Medicine Units (MFMU) Network (American Journal of Perinatology, 2021)
Objective The fetal consequences of intrapartum fetal tachycardia with maternal fever or clinical chorioamnionitis are not well studied. We evaluated the association between perinatal morbidity and fetal tachycardia in the setting of intrapartum fever.Study Design Secondary analysis of a multicenter randomized control trial that enrolled 5,341 healthy laboring nulliparous women ≥36 weeks' gestation. Women with intrapartum fever ≥ 38.0°C (including those meeting criteria for clinical chorioamnionitis) after randomization were included in this analysis. Isolated fetal tachycardia was defined as fetal heart rate (FHR) ≥160 beats per minute for at least 10 minutes in the absence of other FHR abnormalities. FHR abnormalities other than tachycardia were excluded from the analysis. The primary outcome was a perinatal composite (5-minute Apgar's score ≤3, intubation, chest compressions, or mortality). Secondary outcomes included low arterial cord pH (pH < 7.20), base deficit ≥12, and cesarean delivery.Results A total of 986 (18.5%) of women in the trial developed intrapartum fever, and 728 (13.7%) met criteria to be analyzed; of these, 728 women 336 (46.2%) had maternal-fetal medicine (MFM) reviewer-defined fetal tachycardia, and 349 of the 550 (63.5%) women during the final hour of labor had validated software (PeriCALM) defined fetal tachycardia. After adjusting for confounders, isolated fetal tachycardia was not associated with a significant difference in the composite perinatal outcome (adjusted odds ratio [aOR] = 3.15 [0.82–12.03]) compared with absence of tachycardia. Fetal tachycardia was associated with higher odds of arterial cord pH <7.2, aOR = 1.48 (1.01–2.17) and of infants with a base deficit ≥ 12, aOR = 2.42 (1.02–5.77), but no significant difference in the odds of cesarean delivery, aOR = 1.33 (0.97–1.82).Conclusion Fetal tachycardia in the setting of intrapartum fever or chorioamnionitis is associated with significantly increased fetal acidemia defined as a pH <7.2 and base excess ≥12 but not with a composite perinatal morbidity.Key Points
Keywords: intrapartum fever; fever; intrapartum; fetal tachycardia; neonatal morbidity; fetal heart rate monitoring; umbilical artery pH; acidemia; fetal acidemia; base deficit